NBR diaphragm rubber compound for liquefied natural gas and preparation method of NBR diaphragm rubber compound
By using deep treatment of modified carbon black and corrosion inhibitor in the liquefied natural gas diaphragm, combined with polystyrene grafted polybutyl acrylate emulsion and vulcanization accelerator, NBR diaphragm kneading glue with excellent hardness and elasticity were prepared. The problem of insufficient mechanical properties of existing diaphragms in high temperature environments is solved, and the storage and transportation safety of liquefied natural gas is improved.
Patent Information
- Application Number
- CN202411460112.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2024-12-27
AI Technical Summary
The existing natural gas diaphragms have insufficient mechanical performance stability and elasticity in high temperature environments, making it difficult to meet the safe storage and transportation needs of liquefied natural gas.
Using NBR diaphragm mixing glue with liquefied natural gas, including reinforcement, filler, polystyrene grafted polybutyl acrylate emulsion, plasticizer, vulcanization accelerator and other components, the depth of carbon black and corrosion inhibitor is modified. The treatment is combined with high-pressure composite technology to prepare a kneaded glue with excellent hardness, strength and elasticity.
It significantly improves the mechanical properties stability and elasticity of the mixing glue at high temperatures, reduces the sensitivity of strength and hardness to temperature, and provides a more reliable guarantee for liquefied natural gas storage and transportation materials.
Smart Images

Figure BDA0005091628110000161
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of rubber mixes, and in particular to an NBR diaphragm rubber mix for liquefied natural gas and a preparation method thereof. Background Art
[0002] Before natural gas is delivered to end users, mercaptan, tetrahydrothiophene, etc. are used to add odor to natural gas to help detect leaks. Natural gas is lighter than air and easily dispersed. When natural gas gathers in a closed environment such as a house or tent and reaches a certain proportion, it will trigger a powerful explosion. The explosion may flatten the entire house and even affect neighboring buildings. The lower limit of the explosion limit of methane in air is 5% and the upper limit is 15%. Therefore, a diaphragm rubber with good sealing effect resistant to liquefied natural gas is needed.
[0003] For example, Chinese patent CN114292513B discloses a high-tolerance intake manifold diaphragm and its preparation method. The diaphragm material includes the following raw materials by mass: 40-50 parts of chloroether rubber, 2-3 parts of magnesium oxide, 1-2 parts of antioxidant, 15-35 parts of carbon black, 10-15 parts of softener, 3-5 parts of inorganic filler, 0.6-1.3 parts of thiocyanate, and 1.5-2.5 parts of DOTG. The preparation method of the diaphragm material includes the following steps: Step I: adding chloroether rubber to an internal mixer and then plasticizing; Step II: adding magnesium oxide, antioxidant, carbon black, softener, and inorganic filler and then mixing; Step III: adding softener and then continuing to mix; Step IV: adding thiocyanate and DOTG and then continuing to mix to obtain the diaphragm material; the diaphragm material is pressed into a manifold intake system control valve diaphragm by a one-time molding process.
[0004] Although the above patent has a high fatigue resistance at high temperature, that is, it can withstand cyclic loading without breaking under high temperature environment; but the stability of mechanical properties at high temperature still needs to be improved; in addition, the elasticity of the above patent still needs to be improved.
[0005] Based on this, the present invention designs a NBR (nitrile rubber) diaphragm compound for liquefied natural gas and a preparation method thereof to solve the above problems. Summary of the invention
[0006] In view of the above-mentioned shortcomings of the prior art, the present invention provides an NBR diaphragm rubber compound for liquefied natural gas and a preparation method thereof.
[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0008] A NBR diaphragm rubber compound for liquefied natural gas, comprising the following components:
[0009] Reinforcing agent 15.5-25%;
[0010] Filler 5-14.6%;
[0011] Plasticizer 5-10%;
[0012] Polystyrene grafted polybutyl acrylate emulsion 2-5%;
[0013] Compounding agent 5-10%;
[0014] Vulcanization accelerator 1.6-4%;
[0015] The balance is nitrile rubber;
[0016] The mass ratio of the glass microspheres, the modified carbon black and the corrosion inhibitor XHT-1 in the reinforcing agent is 2-3:3-7:1.8-2.6.
[0017] A method for preparing the NBR diaphragm rubber compound for liquefied natural gas comprises the following steps:
[0018] Step 1: preparing modified carbon black;
[0019] Add carbon black to methanol containing p-hydroxyphenylglycine and stir, remove the solvent under vacuum to obtain a mixture A, calcine the mixture A at 500-550° C., and grind to obtain modified carbon black;
[0020] Step 2: preparing a reinforcing agent;
[0021] After the glass microspheres and modified carbon black are fully mixed, the corrosion inhibitor XHT-1 preheated to 45-53°C is added dropwise, and the reinforcing agent is obtained by keeping the temperature at 40-50°C for 10-15 minutes;
[0022] Step 3: preparing a modified plasticizer;
[0023] Preheat the polystyrene grafted polybutyl acrylate emulsion to 56-67°C, add 1 / 3-1 / 2 of the plasticizer and stir evenly, and when it is naturally cooled to 40-45°C, add the remaining plasticizer and stir evenly to obtain a modified plasticizer;
[0024] Step 4: Add the filler to the modified plasticizer, mix thoroughly to obtain a mixture B, put the mixture B in a sealed bag, drive out the bubbles in the sealed bag and seal it, and perform high pressure treatment at 150-200Mpa for 10-20min to obtain a high pressure composite filler;
[0025] Step 5: Add 37.4-51.5 parts of nitrile rubber and 5-10 parts of compounding agent into an internal mixer for mixing; add 15.5-25 parts of reinforcing agent into the internal mixer and mix; add high-pressure composite filler into the internal mixer, unload the material after mixing, and obtain a mixed rubber;
[0026] Step 6: Add 1.6-4 parts of vulcanization accelerator to the rubber mix, mix for 100-120 seconds, and discharge the material to obtain NBR diaphragm rubber mix for liquefied natural gas.
[0027] Furthermore, step one is specifically as follows: adding carbon black to methanol with p-hydroxyphenylglycine, stirring at 40-50°C for 20-30 minutes, removing the solvent under vacuum to obtain mixture A, and calcining mixture A at 500-550°C for 1-2 hours to obtain modified carbon black.
[0028] Furthermore, in step 1, the mass ratio of p-hydroxyphenylglycine, methanol and carbon black is 2-3:40-50:10-15.
[0029] Furthermore, step 2 is specifically as follows: after fully mixing the glass microspheres and modified carbon black in a mass ratio of 2-3:3-7, adding the corrosion inhibitor XHT-1 preheated to 45-53° C. dropwise, and keeping warm at 40-50° C. for 10-15 minutes to obtain the reinforcing agent.
[0030] Furthermore, in step 2, the mass ratio of the glass microspheres to the corrosion inhibitor XHT-1 is 2-3:1.8-2.6.
[0031] Furthermore, step three is specifically as follows: preheating the polystyrene grafted polybutyl acrylate emulsion to 56-67°C, adding 1 / 3-1 / 2 of the plasticizer and stirring evenly at a speed of 200-300r / min, and when naturally cooled to 40-45°C, adding the remaining plasticizer and stirring evenly at a speed of 200-300r / min to obtain a modified plasticizer.
[0032] Furthermore, step five is specifically as follows: 37.4-51.5 parts of nitrile rubber and 5-10 parts of compounding agent are added into an internal mixer for mixing for 50-60 seconds; 15.5-25 parts of reinforcing agent are added into the internal mixer for mixing for 60-80 seconds; high-pressure composite filler is added into the internal mixer, and after mixing for 80-140 seconds, the material is discharged into sheets to obtain a mixed rubber.
[0033] Furthermore, the vulcanization accelerator is one or more of TMTD-75, CBS-80 and EC-80GE.
[0034] Furthermore, the compounding agent is a composition of zinc oxide, stearic acid, antioxidant KY-405, antioxidant 4010NA, anti-cracking agent B-10 and auxiliary agent NB109 in a mass ratio of 2:3:5:4:7:5.
[0035] Compared with the prior art, the present invention has the following beneficial effects: 1. The NBR diaphragm rubber compound for liquefied natural gas prepared by the present invention has excellent hardness and strength as its cornerstone, and can firmly maintain its mechanical properties, including the stability of hardness and strength, even in a high temperature environment, and exhibits excellent heat resistance stability. At the same time, the rubber compound also has excellent elasticity and excellent comprehensive performance.
[0036] 2. The present invention greatly improves the stability of the rubber mix under high temperature conditions by introducing a compound of polystyrene and plasticizer, and effectively reduces the sensitivity of strength and hardness to temperature. By using the corrosion inhibitor XHT-1 to deeply modify the glass microspheres and modified carbon black, the rubber mix is successfully endowed with more excellent elastic properties. The flexibility and durability of the rubber mix are improved, providing a more reliable material guarantee for the safe storage and transportation of liquefied natural gas. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] Example 1
[0039] This embodiment provides a method for preparing an NBR diaphragm rubber compound for liquefied natural gas, comprising the following steps:
[0040] Step 1: preparing modified carbon black;
[0041] Add carbon black to methanol containing p-hydroxyphenylglycine, stir at 50°C for 30 minutes, remove the solvent under vacuum to obtain a mixture A, calcine the mixture A at 550°C for 2 hours, and grind to obtain modified carbon black;
[0042] The mass ratio of p-hydroxyphenylglycine to methanol is 3:50;
[0043] The mass ratio of p-hydroxyphenylglycine to carbon black is 3:15;
[0044] Step 2: preparing a reinforcing agent;
[0045] After the glass microspheres and modified carbon black in a mass ratio of 3:7 are fully mixed, 300 mg / L of corrosion inhibitor XHT-1 preheated to 53°C is added dropwise, and the mixture is dripped over 20 minutes. The mixture is kept at 50°C for 15 minutes to obtain a reinforcing agent. The mass ratio of glass microspheres to corrosion inhibitor XHT-1 is 3:2.6.
[0046] Step 3: preparing a modified plasticizer;
[0047] Preheat 3 kg of polystyrene grafted polybutyl acrylate emulsion to 67° C., add 1 / 2 of the plasticizer (total amount of 7.4 kg) and stir evenly at a speed of 300 r / min. When naturally cooled to 45° C., add the remaining plasticizer and stir evenly at a speed of 300 r / min to obtain a modified plasticizer;
[0048] Step 4: Add 14.6 kg of filler to the modified plasticizer, mix thoroughly to obtain mixture B, put mixture B in a sealed bag, drive out the bubbles in the sealed bag and seal it, and perform high pressure treatment at 200 MPa for 20 minutes to obtain a high pressure composite filler;
[0049] Step 5: Add 51.5 kg of nitrile rubber and 5 kg of compounding agent into an internal mixer for mixing for 60 seconds; add 15.5 kg of reinforcing agent into the internal mixer and mix for 80 seconds; add high-pressure composite filler into the internal mixer, mix for 140 seconds, and then discharge the material into sheets to obtain a mixed rubber;
[0050] Step 6: Add 3 kg of vulcanization accelerator (TMTD-75) to the rubber mix, mix for 120 seconds, and discharge the material to obtain NBR diaphragm rubber mix for liquefied natural gas.
[0051] The compounding agent is a composition of zinc oxide, stearic acid, antioxidant KY-405, antioxidant 4010NA, anti-cracking agent B-10 and auxiliary agent NB109 (Moken NB109, Lechuan (Langfang) International Trade Co., Ltd.) in a mass ratio of 2:3:5:4:7:5;
[0052] The plasticizer is TP-90B;
[0053] The carbon black is Orion HS25 carbon black;
[0054] The filler is CREATE-E1;
[0055] The polystyrene grafted polybutyl acrylate emulsion is selected from Xiong Huixia, Zhao Wenjie. Performance and microstructure analysis of cement mortar modified by polystyrene grafted polybutyl acrylate emulsion[J]. China Plastics, 2021, 35(02): 29-33. DOI: 10.19491 / j.issn.1001-9278.2021.02.005.
[0056] The new corrosion inhibitor XHT-1 is selected from Zhang Wen, Lin Jun, Wu Tong. Preparation and performance study of new corrosion inhibitor for natural gas transmission pipeline[J]. Chemical Engineer, 2024, 38(08): 13-17. DOI: 10.16247 / j.cnki.23-1171 / tq.20240813.
[0057] HPP.L2-600 / 2 ultrahigh pressure equipment was used for high pressure treatment, Tianjin Huatai Senmiao Bioengineering Technology Co., Ltd.
[0058] Krynac 3370C adopts a special manufacturing process. This grade of NBR rubber has excellent oil resistance, heat resistance, good processing safety, excellent wear resistance and puncture resistance. It is suitable for high temperature resistant, medium resistant, low pressure change products, such as sealing rings and rubber diaphragms.
[0059] Orion HS-25 carbon black has higher modulus and lower sieve residue than N774, which helps to reduce the sand hole particles in the diaphragm, better elasticity and resistance to compression permanent deformation. HS-25 carbon black has a larger particle size in the N700 series, good mechanical properties, small deformation during extrusion and injection molding, and good surface smoothness.
[0060] The main component of CREATE-E1 is lamellar SiO2, which has a softening effect on the rubber compound. Under shear stress, it is conducive to the relative slippage of the rubber macromolecular chain and improves the mold filling performance of the rubber compound. After surface treatment with silane coupling agent, titanate coupling agent and stearic acid, CREATE-E1 has reduced surface hydrophilicity, good bonding with rubber, and reduces the viscosity of the rubber compound. In addition, the lamellar structure also helps to reduce the penetration and leakage of natural gas, and assists in achieving a better sealing effect.
[0061] Rohm and Haas TP-90B is used as a plasticizer in rubber to provide rubber with excellent low-temperature adaptability, that is, the rubber is very soft at low temperatures and will not seep out of the rubber at extremely low temperatures, preventing the diaphragm from being too hard and causing valve failure when the temperature is too low. TP-90B is easily dispersed in the rubber, is not affected by vulcanization, and will not reduce the physical properties of the rubber. TP-90B can also be used as an antistatic agent to improve the antistatic effect of rubber products. It can be used as a bactericide in chloroprene rubber to inhibit the growth of fungi.
[0062] KY-405 is a non-polluting amine antioxidant with good protection against aging caused by heat, light, ozone, etc. Antioxidant 4010NA is a general-purpose excellent antioxidant in the field of natural rubber, synthetic rubber and latex. It has excellent protection against ozone and flex fatigue aging, and also has good protection against harmful metals such as thermal oxygen, copper, and manganese. The protective wax B-10 has a high content of isomerized and cyclized hydrocarbons and a slow migration rate. It can effectively prevent or delay the surface atomization and frosting of rubber products caused by wax. After vulcanization, it can form a uniform and dense protective film attached to the surface of rubber products. It has high adhesion and is not easy to fall off. It can effectively resist ozone aging and prevent cracking on the surface of products. It has a long-lasting protective effect. Moken NB109 is an internal addition release agent specially developed for nitrile rubber. It has good compatibility with the rubber material and will not affect the physical properties of the rubber material. It can assist the effective dispersion of fillers and improve the fluidity of the rubber material. Moken NB109 can effectively improve the demoulding performance of nitrile rubber, greatly reduce the mold contamination problem during the vulcanization process, improve product yield, and reduce the risk of diaphragm leakage.
[0063] Example 2
[0064] This embodiment provides a method for preparing an NBR diaphragm rubber compound for liquefied natural gas, comprising the following steps:
[0065] Step 1: preparing modified carbon black;
[0066] Add carbon black to methanol containing p-hydroxyphenylglycine, stir at 40°C for 20 minutes, remove the solvent under vacuum to obtain a mixture A, calcine the mixture at 500°C for 1 hour, and grind to obtain modified carbon black;
[0067] The mass ratio of p-hydroxyphenylglycine to methanol is 2:40;
[0068] The mass ratio of p-hydroxyphenylglycine to carbon black is 2:10;
[0069] Step 2: preparing a reinforcing agent;
[0070] After the glass microspheres and modified carbon black in a mass ratio of 2:3 are fully mixed, 300 mg / L of corrosion inhibitor XHT-1 preheated to 45°C is added dropwise, and the mixture is dripped over 20 minutes. The mixture is kept at 40°C for 10 minutes to obtain a reinforcing agent. The mass ratio of the glass microspheres to the corrosion inhibitor XHT-1 is 2:1.8.
[0071] Step 3: preparing a modified plasticizer;
[0072] Preheat 4 kg of polystyrene grafted polybutyl acrylate emulsion to 56° C., add 1 / 3 of plasticizer (total amount of 7.7 kg) and stir evenly at a speed of 200 r / min, and when naturally cooled to 40° C., add the remaining plasticizer and stir evenly at a speed of 200 r / min to obtain a modified plasticizer;
[0073] Step 4: Add 5 kg of filler to the modified plasticizer, mix thoroughly to obtain mixture B, put mixture B in a sealed bag, drive out the bubbles in the sealed bag and seal it, and perform high pressure treatment at 150 MPa for 10 minutes to obtain a high pressure composite filler;
[0074] Step 5: 37.4 kg of nitrile rubber and 5 kg of compounding agent are added to an internal mixer for mixing for 50 seconds; 15.5 kg of reinforcing agent is added to the internal mixer for mixing for 60 seconds; high-pressure composite filler is added to the internal mixer, and after mixing for 80 seconds, the material is discharged to obtain a mixed rubber;
[0075] Step 6: Add 2.7 kg of vulcanization accelerator (CBS-80) to the rubber mix, mix for 100 seconds, and discharge the material to obtain NBR diaphragm rubber mix for liquefied natural gas.
[0076] The compounding agent is a composition of zinc oxide, stearic acid, antioxidant KY-405, antioxidant 4010NA, anti-cracking agent B-10 and auxiliary agent NB109 (Moken NB109, Lechuan (Langfang) International Trade Co., Ltd.) in a mass ratio of 2:3:5:4:7:5;
[0077] The plasticizer is TP-90B;
[0078] The carbon black is Orion HS25 carbon black;
[0079] The filler is CREATE-E1;
[0080] The polystyrene grafted polybutyl acrylate emulsion is selected from Xiong Huixia, Zhao Wenjie. Performance and microstructure analysis of cement mortar modified by polystyrene grafted polybutyl acrylate emulsion[J]. China Plastics, 2021, 35(02): 29-33. DOI: 10.19491 / j.issn.1001-9278.2021.02.005.
[0081] The new corrosion inhibitor XHT-1 is selected from Zhang Wen, Lin Jun, Wu Tong. Preparation and performance study of new corrosion inhibitor for natural gas transmission pipeline[J]. Chemical Engineer, 2024, 38(08): 13-17. DOI: 10.16247 / j.cnki.23-1171 / tq.20240813.
[0082] Example 3
[0083] This embodiment provides a method for preparing an NBR diaphragm rubber compound for liquefied natural gas, comprising the following steps:
[0084] Step 1: preparing modified carbon black;
[0085] Add carbon black to methanol containing p-hydroxyphenylglycine, stir at 48°C for 22 minutes, remove the solvent under vacuum to obtain a mixture A, calcine the mixture at 520°C for 1.2 hours, and grind to obtain modified carbon black;
[0086] The mass ratio of p-hydroxyphenylglycine to methanol is 2:46;
[0087] The mass ratio of p-hydroxyphenylglycine to carbon black is 2:12;
[0088] Step 2: preparing a reinforcing agent;
[0089] After the glass microspheres and modified carbon black in a mass ratio of 2:6 are fully mixed, 300 mg / L of corrosion inhibitor XHT-1 preheated to 48°C is added dropwise, and the mixture is dripped over 20 minutes, and then kept at 44°C for 12 minutes to obtain a reinforcing agent; the mass ratio of glass microspheres to corrosion inhibitor XHT-1 is 2:2.2;
[0090] Step 3: preparing a modified plasticizer;
[0091] Preheat 5 kg of polystyrene grafted polybutyl acrylate emulsion to 62°C, add 1 / 2 of plasticizer (total amount is 10 kg) and stir evenly at a speed of 240 r / min, and when it is naturally cooled to 42°C, add the remaining plasticizer and stir evenly at a speed of 230 r / min to obtain a modified plasticizer;
[0092] Step 4: Add 5-14.6 kg of filler to the modified plasticizer, mix thoroughly to obtain mixture B, put mixture B in a sealed bag, drive out the bubbles in the sealed bag and seal it, and perform high pressure treatment at 180 MPa for 12 minutes to obtain a high pressure composite filler;
[0093] Step 5: 40.6 kg of nitrile rubber and 6.5 kg of compounding agent are added to an internal mixer for mixing for 53 seconds; 25 kg of reinforcing agent is added to the internal mixer for mixing for 70 seconds; high-pressure composite filler is added to the internal mixer, and after mixing for 100 seconds, the material is discharged to obtain a mixed rubber;
[0094] Step 6: Add 1.6 kg of vulcanization accelerator (EC-80GE) to the rubber mix, mix for 115 seconds, and discharge the material to obtain NBR diaphragm rubber mix for liquefied natural gas.
[0095] The compounding agent is a composition of zinc oxide, stearic acid, antioxidant KY-405, antioxidant 4010NA, anti-cracking agent B-10 and auxiliary agent NB109 (Moken NB109, Lechuan (Langfang) International Trade Co., Ltd.) in a mass ratio of 2:3:5:4:7:5;
[0096] The plasticizer is TP-90B;
[0097] The carbon black is Orion HS25 carbon black;
[0098] The filler is CREATE-E1;
[0099] The polystyrene grafted polybutyl acrylate emulsion is selected from Xiong Huixia, Zhao Wenjie. Performance and microstructure analysis of cement mortar modified by polystyrene grafted polybutyl acrylate emulsion[J]. China Plastics, 2021, 35(02): 29-33. DOI: 10.19491 / j.issn.1001-9278.2021.02.005.
[0100] The new corrosion inhibitor XHT-1 is selected from Zhang Wen, Lin Jun, Wu Tong. Preparation and performance study of new corrosion inhibitor for natural gas transmission pipeline[J]. Chemical Engineer, 2024, 38(08): 13-17. DOI: 10.16247 / j.cnki.23-1171 / tq.20240813.
[0101] Example 4
[0102] This embodiment provides a method for preparing an NBR diaphragm rubber compound for liquefied natural gas, comprising the following steps:
[0103] Step 1: preparing modified carbon black;
[0104] Add carbon black to methanol containing p-hydroxyphenylglycine, stir at 47°C for 24 minutes, remove the solvent under vacuum to obtain a mixture A, calcine the mixture at 540°C for 1.5 hours, and grind to obtain modified carbon black;
[0105] The mass ratio of p-hydroxyphenylglycine to methanol is 2:46;
[0106] The mass ratio of p-hydroxyphenylglycine to carbon black is 2:14;
[0107] Step 2: preparing a reinforcing agent;
[0108] After the glass microspheres and modified carbon black in a mass ratio of 2:6 are fully mixed, 300 mg / L of corrosion inhibitor XHT-1 preheated to 48°C is added dropwise, and the mixture is dripped over 20 minutes, and then kept at 42°C for 13 minutes to obtain a reinforcing agent; the mass ratio of glass microspheres to corrosion inhibitor XHT-1 is 2:2.1;
[0109] Step 3: preparing a modified plasticizer;
[0110] Preheat 2 kg of polystyrene grafted polybutyl acrylate emulsion to 58°C, add 1 / 2 of plasticizer (total amount of 5 kg) and stir evenly at a speed of 210 r / min, and when naturally cooled to 44°C, add the remaining plasticizer and stir evenly at a speed of 220 r / min to obtain a modified plasticizer;
[0111] Step 4: Add 11.3 kg of filler to the modified plasticizer, mix thoroughly to obtain mixture B, put mixture B in a sealed bag, drive out the bubbles in the sealed bag and seal it, and perform high pressure treatment at 170 MPa for 18 minutes to obtain a high pressure composite filler;
[0112] Step 5: 40.6 kg of nitrile rubber and 6.5 kg of compounding agent are added to an internal mixer for mixing for 56 seconds; 25 kg of reinforcing agent is added to the internal mixer for mixing for 74 seconds; high-pressure composite filler is added to the internal mixer, and after mixing for 130 seconds, the material is discharged to obtain a mixed rubber;
[0113] Step 6: Add 1.6 kg of vulcanization accelerator CBS-80 to the rubber mix, mix for 120 seconds, and discharge the material to obtain NBR diaphragm rubber mix for liquefied natural gas.
[0114] The compounding agent is a composition of zinc oxide, stearic acid, antioxidant KY-405, antioxidant 4010NA, anti-cracking agent B-10 and auxiliary agent NB109 (Moken NB109, Lechuan (Langfang) International Trade Co., Ltd.) in a mass ratio of 2:3:5:4:7:5;
[0115] The plasticizer is TP-90B;
[0116] The carbon black is Orion HS25 carbon black;
[0117] The filler is CREATE-E1;
[0118] The polystyrene grafted polybutyl acrylate emulsion is selected from Xiong Huixia, Zhao Wenjie. Performance and microstructure analysis of cement mortar modified by polystyrene grafted polybutyl acrylate emulsion[J]. China Plastics, 2021, 35(02): 29-33. DOI: 10.19491 / j.issn.1001-9278.2021.02.005.
[0119] The new corrosion inhibitor XHT-1 is selected from Zhang Wen, Lin Jun, Wu Tong. Preparation and performance study of new corrosion inhibitor for natural gas transmission pipeline[J]. Chemical Engineer, 2024, 38(08): 13-17. DOI: 10.16247 / j.cnki.23-1171 / tq.20240813.
[0120] Comparative Example 1
[0121] The difference from Example 2 is that the polystyrene grafted polybutyl acrylate emulsion is not added in this comparative example.
[0122] This comparative example provides a method for preparing an NBR diaphragm rubber compound for liquefied natural gas, comprising the following steps:
[0123] Step 1: preparing modified carbon black;
[0124] Add carbon black to methanol containing p-hydroxyphenylglycine, stir at 40°C for 20 minutes, remove the solvent under vacuum to obtain a mixture A, calcine the mixture at 500°C for 1 hour, and grind to obtain modified carbon black;
[0125] The mass ratio of p-hydroxyphenylglycine to methanol is 2:40;
[0126] The mass ratio of p-hydroxyphenylglycine to carbon black is 2:10;
[0127] Step 2: preparing a reinforcing agent;
[0128] After the glass microspheres and modified carbon black in a mass ratio of 2:3 are fully mixed, 300 mg / L of corrosion inhibitor XHT-1 preheated to 45°C is added dropwise, and the mixture is dripped over 20 minutes. The mixture is kept at 40°C for 10 minutes to obtain a reinforcing agent. The mass ratio of the glass microspheres to the corrosion inhibitor XHT-1 is 2:1.8.
[0129] Step 3: preparing a modified plasticizer;
[0130] Preheat 1 / 2 of the plasticizer (total amount of 7.7 kg) to 56°C and stir evenly at a speed of 200 r / min. When naturally cooled to 40°C, add the remaining plasticizer and stir evenly at a speed of 200 r / min to obtain a modified plasticizer;
[0131] Step 4: Add 5 kg of filler to the modified plasticizer, mix thoroughly to obtain mixture B, put mixture B in a sealed bag, drive out the bubbles in the sealed bag and seal it, and perform high pressure treatment at 150 MPa for 10 minutes to obtain a high pressure composite filler;
[0132] Step 5: 37.4 kg of nitrile rubber and 5 kg of compounding agent are added to an internal mixer for mixing for 50 seconds; 15.5 kg of reinforcing agent is added to the internal mixer for mixing for 60 seconds; high-pressure composite filler is added to the internal mixer, and after mixing for 80 seconds, the material is discharged to obtain a mixed rubber;
[0133] Step 6: Add 2.7 kg of vulcanization accelerator (CBS-80) to the rubber mix, mix for 100 seconds, and discharge the material to obtain NBR diaphragm rubber mix for liquefied natural gas.
[0134] The compounding agent is a composition of zinc oxide, stearic acid, antioxidant KY-405, antioxidant 4010NA, anti-cracking agent B-10 and auxiliary agent NB109 (Moken NB109, Lechuan (Langfang) International Trade Co., Ltd.) in a mass ratio of 2:3:5:4:7:5;
[0135] The plasticizer is TP-90B;
[0136] The carbon black is Orion HS25 carbon black;
[0137] The filler is CREATE-E1;
[0138] The polystyrene grafted polybutyl acrylate emulsion is selected from Xiong Huixia, Zhao Wenjie. Performance and microstructure analysis of cement mortar modified by polystyrene grafted polybutyl acrylate emulsion[J]. China Plastics, 2021, 35(02): 29-33. DOI: 10.19491 / j.issn.1001-9278.2021.02.005.
[0139] The new corrosion inhibitor XHT-1 is selected from Zhang Wen, Lin Jun, Wu Tong. Preparation and performance study of new corrosion inhibitor for natural gas transmission pipeline[J]. Chemical Engineer, 2024, 38(08): 13-17. DOI: 10.16247 / j.cnki.23-1171 / tq.20240813.
[0140] Comparative Example 2
[0141] The difference from Example 2 is that the corrosion inhibitor XHT-1 is not added in this comparative example.
[0142] This comparative example provides a method for preparing an NBR diaphragm rubber compound for liquefied natural gas, comprising the following steps:
[0143] Step 1: preparing modified carbon black;
[0144] Add carbon black to methanol containing p-hydroxyphenylglycine, stir at 40°C for 20 minutes, remove the solvent under vacuum to obtain a mixture A, calcine the mixture at 500°C for 1 hour, and grind to obtain modified carbon black;
[0145] The mass ratio of p-hydroxyphenylglycine to methanol is 2:40;
[0146] The mass ratio of p-hydroxyphenylglycine to carbon black is 2:10;
[0147] Step 2: preparing a reinforcing agent;
[0148] After the glass microspheres and modified carbon black in a mass ratio of 2:3 are fully mixed, the mixture is preheated to 45°C for 20 minutes and then kept at 40°C for 10 minutes to obtain a reinforcing agent;
[0149] Step 3: preparing a modified plasticizer;
[0150] Preheat 4 kg of polystyrene grafted polybutyl acrylate emulsion to 56° C., add 1 / 2 of the plasticizer (total amount of 7.7 kg) and stir evenly at a speed of 200 r / min. When naturally cooled to 40° C., add the remaining plasticizer and stir evenly at a speed of 200 r / min to obtain a modified plasticizer;
[0151] Step 4: Add 5 kg of filler to the modified plasticizer, mix thoroughly to obtain mixture B, put mixture B in a sealed bag, drive out the bubbles in the sealed bag and seal it, and perform high pressure treatment at 150 MPa for 10 minutes to obtain a high pressure composite filler;
[0152] Step 5: 37.4 kg of nitrile rubber and 5 kg of compounding agent are added to an internal mixer for mixing for 50 seconds; 15.5 kg of reinforcing agent is added to the internal mixer for mixing for 60 seconds; high-pressure composite filler is added to the internal mixer, and after mixing for 80 seconds, the material is discharged to obtain a mixed rubber;
[0153] Step 6: Add 2.7 kg of vulcanization accelerator (CBS-80) to the rubber mix, mix for 100 seconds, and discharge the material to obtain NBR diaphragm rubber mix for liquefied natural gas.
[0154] The compounding agent is a composition of zinc oxide, stearic acid, antioxidant KY-405, antioxidant 4010NA, anti-cracking agent B-10 and auxiliary agent NB109 (Moken NB109, Lechuan (Langfang) International Trade Co., Ltd.) in a mass ratio of 2:3:5:4:7:5;
[0155] The plasticizer is TP-90B;
[0156] The carbon black is Orion HS25 carbon black;
[0157] The filler is CREATE-E1;
[0158] The polystyrene grafted polybutyl acrylate emulsion is selected from Xiong Huixia, Zhao Wenjie. Performance and microstructure analysis of cement mortar modified by polystyrene grafted polybutyl acrylate emulsion[J]. China Plastics, 2021, 35(02): 29-33. DOI: 10.19491 / j.issn.1001-9278.2021.02.005.
[0159] The new corrosion inhibitor XHT-1 is selected from Zhang Wen, Lin Jun, Wu Tong. Preparation and performance study of new corrosion inhibitor for natural gas transmission pipeline[J]. Chemical Engineer, 2024, 38(08): 13-17. DOI: 10.16247 / j.cnki.23-1171 / tq.20240813.
[0160] Experimental example
[0161] The performance tests of the rubber compounds obtained in Examples 1-4 and Comparative Examples 1-2 were performed, and the results were as follows:
[0162]
[0163] The NBR diaphragm rubber compound for liquefied natural gas prepared by the invention has high hardness and strength, is resistant to n-pentane and high temperature, has high elasticity and excellent comprehensive performance; the high temperature resistance of the rubber compound is improved by adding polystyrene grafted polybutyl acrylate emulsion and compounding with a plasticizer; the elasticity of the rubber compound is effectively improved by modifying the glass microspheres and modified carbon black with a corrosion inhibitor XHT-1.
[0164] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A NBR diaphragm rubber compound for liquefied natural gas, characterized in that: Includes the following components: Reinforcing agent 15.5-25%; Filler 5-14.6%; Plasticizer 5-10%; Polystyrene grafted polybutyl acrylate emulsion 2-5%; Compounding agent 5-10%; Vulcanization accelerator 1.6-4%; The balance is nitrile rubber; The mass ratio of the glass microspheres, the modified carbon black and the corrosion inhibitor XHT-1 in the reinforcing agent is 2-3:3-7:1.8-2.
6.
2. A method for preparing the NBR diaphragm rubber compound for liquefied natural gas as claimed in claim 1, characterized in that: The following steps are involved: Step 1: preparing modified carbon black; Add carbon black to methanol containing p-hydroxyphenylglycine and stir, remove the solvent under vacuum to obtain a mixture A, calcine the mixture A at 500-550° C., and grind to obtain modified carbon black; Step 2: preparing a reinforcing agent; After the glass microspheres and modified carbon black are fully mixed, the corrosion inhibitor XHT-1 preheated to 45-53°C is added dropwise, and the reinforcing agent is obtained by keeping the temperature at 40-50°C for 10-15 minutes; Step 3: preparing a modified plasticizer; Preheat the polystyrene grafted polybutyl acrylate emulsion to 56-67°C, add 1 / 3-1 / 2 of the plasticizer and stir evenly, and when it is naturally cooled to 40-45°C, add the remaining plasticizer and stir evenly to obtain a modified plasticizer; Step 4: Add the filler to the modified plasticizer, mix thoroughly to obtain a mixture B, put the mixture B in a sealed bag, drive out the bubbles in the sealed bag and seal it, and perform high pressure treatment at 150-200Mpa for 10-20min to obtain a high pressure composite filler; Step 5: Add 37.4-51.5 parts of nitrile rubber and 5-10 parts of compounding agent into an internal mixer for mixing; add 15.5-25 parts of reinforcing agent into the internal mixer and mix; add high-pressure composite filler into the internal mixer, unload the material after mixing, and obtain a mixed rubber; Step 6: Add 1.6-4 parts of vulcanization accelerator to the rubber mix, mix for 100-120 seconds, and discharge the material to obtain NBR diaphragm rubber mix for liquefied natural gas.
3. The preparation method according to claim 2, characterized in that: Step 1 is specifically as follows: add carbon black to methanol with p-hydroxyphenylglycine, stir at 40-50° C. for 20-30 min, remove the solvent under vacuum to obtain mixture A, and calcine the mixture A at 500-550° C. for 1-2 h to obtain modified carbon black.
4. The preparation method according to claim 3, characterized in that: In step 1, the mass ratio of p-hydroxyphenylglycine, methanol and carbon black is 2-3:40-50:10-15.
5. The preparation method according to claim 4, characterized in that: Step 2 is specifically as follows: after fully mixing the glass microspheres and modified carbon black in a mass ratio of 2-3:3-7, adding the corrosion inhibitor XHT-1 preheated to 45-53° C. dropwise, and keeping warm at 40-50° C. for 10-15 minutes to obtain the reinforcing agent.
6. The preparation method according to claim 5, characterized in that: In step 2, the mass ratio of the vitrified microspheres to the corrosion inhibitor XHT-1 is 2-3:1.8-2.
6.
7. The preparation method according to claim 6, characterized in that: Step three is as follows: preheat the polystyrene grafted polybutyl acrylate emulsion to 56-67°C, add 1 / 3-1 / 2 of the plasticizer and stir evenly at a speed of 200-300r / min, and when it is naturally cooled to 40-45°C, add the remaining plasticizer and stir evenly at a speed of 200-300r / min to obtain a modified plasticizer.
8. The preparation method according to claim 7, characterized in that: Step five is as follows: 37.4-51.5 parts of nitrile rubber and 5-10 parts of compounding agent are added into an internal mixer for mixing for 50-60 seconds; 15.5-25 parts of reinforcing agent are added into the internal mixer for mixing for 60-80 seconds; high-pressure composite filler is added into the internal mixer, and after mixing for 80-140 seconds, the material is discharged into sheets to obtain a mixed rubber.
9. The preparation method according to claim 8, characterized in that: The vulcanization accelerator is one or more of TMTD-75, CBS-80 and EC-80GE.
10. The preparation method according to claim 9, characterized in that: The compounding agent is a composition of zinc oxide, stearic acid, antioxidant KY-405, antioxidant 4010NA, anti-cracking agent B-10 and auxiliary agent NB109 in a mass ratio of 2:3:5:4:7:5.
Citation Information
Patent Citations
A high-resistance intake manifold diaphragm and its preparation method
CN114292513B
